George R. Donnan, Annotated Code of Criminal Procedure and Penal Code of the State of New York as Amended 1882-5. Fourth Edition, pg. 298, tit. 12, § 409 (1885) - (:unkn) unknown (General Publisher, 1885)
A person who manufactures, or causes to be manufactured, or sells or keeps for sale, or offers, or gives, or disposes of, any instrument or weapon of the kind usually known as slung-shot, billy, sand club or metal knuckles, or who, in any city in this state, without the written consent of a police magistrate, sells or gives any pistol or other fire-arm to any person under the age of eighteen years is guilty of a misdemeanor.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION